2017
DOI: 10.1159/000471838
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin: Homeostasis and Diseases Related to Iron Metabolism

Abstract: Iron is an essential metal for cell survival that is regulated by the peptide hormone hepcidin. However, its influence on certain diseases is directly related to iron metabolism or secondary to underlying diseases. Genetic alterations influence the serum hepcidin concentration, which can lead to an iron overload in tissues, as observed in haemochromatosis, in which serum hepcidin or defective hepcidin synthesis is observed. Another genetic imbalance of iron is iron-refractory anaemia, in which serum concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 201 publications
(222 reference statements)
0
56
0
6
Order By: Relevance
“…The protein hepcidin is a key regulator of mammalian iron metabolism (Ganz, ; Ganz & Nemeth, ; Michels et al ., ; Reichert et al ., ; Vyoral & Jiri, ; Zaritsky et al ., ). As Zughaier et al .…”
Section: Step –2b External Stresses and A Possible Role For Vitamin Dmentioning
confidence: 99%
“…The protein hepcidin is a key regulator of mammalian iron metabolism (Ganz, ; Ganz & Nemeth, ; Michels et al ., ; Reichert et al ., ; Vyoral & Jiri, ; Zaritsky et al ., ). As Zughaier et al .…”
Section: Step –2b External Stresses and A Possible Role For Vitamin Dmentioning
confidence: 99%
“…The BMP/SMAD pathway, which mediates hepcidin upregulation by iron and hypoxia was also documented to be critical for hepcidin production, besides the erythropoietic pathway which decreases hepcidin level following an increase in the rate of erythropoiesis [11,20,21]. Cancer stimulates the synthesis of many inflammatory cytokines, including IL-1, IL-6 and TNF-α [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that increased serum hepcidin was related to multiple cancers, such as breast cancer, myeloma, renal cell carcinoma and prostate cancer [7][8][9][10]. Hepcidin is homeostatically regulated by iron and erythropoietic activity as well as inflammatory cytokines [9,11]. Hepcidin inhibits iron absorption from the duodenum and iron egress from macrophages and hepatocytes through binding and inducing degradation of iron exporter ferroportin [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, su exceso genera estrés oxidativo, que es también dañino para la función y supervivencia de las células y tejidos. Por ello es importante mantener la homeostasis del hierro (Figura 2) (14,15) . Uno de los mecanismos que utiliza el organismo para mantener la homeostasis del hierro es evitar su excreción; así, las pérdidas por descamación de células entéricas y otras son del nivel de 1 mg diario, que es lo que habría que reponer con la dieta.…”
Section: Requerimiento De Hierrounclassified